Project Writing and Dissertation Supervision: Obligation and Expectations of Project Supervisors, Discussion of Findings, Recommendations, Conclusion and Referencing/Citation - Davies, Joseph (European Journal of Applied Sciences, 2025)
Some of the major challenges of project/dissertation writing of undergraduate students in universities are the presentation of results, discussion of findings and referencing or citation of sources used in the text of their research work. This paper examined the challenges faced by project or undergraduate dissertation supervisors and identified the framework of their obligations and expectations in the process of supervision. However, these challenges has given rise to a lot of poor-quality projects or dissertation work by undergraduate students in most universities across the world. Nonetheless, this paper seek to present a concise context on how to overcome challenges on discussion of research findings, referencing or citation of sources with the examples on the use of different reference styles and a guide on how supervisors should help their undergraduate students produce quality research work.